Предмет: Алгебра,
автор: Аноним
Помогите!!!!!!!!!!!!!!!!!!!!!!!!!!!!!
Приложения:
Ответы
Автор ответа:
0
x² - 5x + 3 = 0
По теореме Виета :
x₁ * x₂ = 3
x₁ + x₂ = 5
3x₁ + 3x₂ - 4x₁x₂ = 3(x₁ + x₂) - 4x₁x₂ = 3 * 5 - 4 * 3 = 15 - 12 = 3
x² - ax - 16 = 0
x₁ * x₂ = - 16
или a₁ = - (2 - 8) = 6 или a₂ = - (- 2 + 8) = - 6
По теореме Виета :
x₁ * x₂ = 3
x₁ + x₂ = 5
3x₁ + 3x₂ - 4x₁x₂ = 3(x₁ + x₂) - 4x₁x₂ = 3 * 5 - 4 * 3 = 15 - 12 = 3
x² - ax - 16 = 0
x₁ * x₂ = - 16
или a₁ = - (2 - 8) = 6 или a₂ = - (- 2 + 8) = - 6
Похожие вопросы
Предмет: Алгебра,
автор: adilhanmoralov
Предмет: История,
автор: anitadizainer11
Предмет: Астрономия,
автор: kksenaya
Предмет: Алгебра,
автор: rakiyapav
Предмет: Обществознание,
автор: nastysmil2015